52 Ovarian Follicular Profiling of High- and Low-immunocrit Gilts on Postnatal Day 14. (7th May 2021) - Lynnes, Brianna M; Cushman, Robert A; Miles, Jeremy R; Oliver, William T; Bartol, Frank F; Bagnell, Carol A; Lents, Clay A
Abstract: Colostrum intake by neonatal piglets can be measured using the immunoglobulin immunocrit assay (iCrit). Lactocrine effects occur when maternally derived, milk-borne bioactive factors are transferred to the neonatal circulation with consumption of colostrum during nursing and affect development of somatic tissues, which can have long-term consequences in adulthood. Lactocrine deficiency, indicated by low neonatal iCrit, altered uterine gene expression and reduced fecundity in adult, neonatally lactocrine-deficient gilts. Litter size in pigs is dependent on both ovarian and uterine function. It was hypothesized that lactocrine deficiency affects development of ovarian follicles in gilts. The objective was to determine the number of primordial, primary, and secondary follicles in ovaries of gilts with high (12% ± 0.5; n = 10) or low (1.9% ± 0.4; n = 10) iCrit, determined on postnatal day (PND) 1 after birth. Paired high- and low-iCrit gilts were chosen from the same litters (birth weight; 3.1 ± 0.2 lbs). On PND 14, ovaries were collected and histological sections prepared (3 sections per animal; 30–150 µm apart). Ovarian follicles in each section were staged and the number of follicles in each category were quantified and subjected to ANOVA. Total number of ovarian follicles did not differ with iCrit (P = 0.55; 1, 370.6 ± 147.8 follicles per section). The proportion of primordial, primary, and secondary follicles was 89.6 ± 1.15%, 7.7 ± 0.87%, 2.7 ± 0.51%, respectively. The number of primordial (P = 0.55), primary (P = 0.64), and secondary (P = 0.93) follicles did not differ with iCrit. Results indicate that ovarian follicular development of neonatal gilts is not sensitive to immunocrit status. Although lactocrine deficiency did not influence the ovarian follicular profile at PND 14, it remains unknown whether lactocrine programming alters ovarian follicular dynamics in neonatally lactocrine-deficient adults. USDA is an equal opportunity provider and employer.